Global long-run convergence of carbon emissions and intensity vis-à-vis countries' industrial profiles - Yigang Wei; Tsun Se Cheong; Michal Wojewodzki; Xunpeng Shi (Green Finance)
We examined distribution dynamics and the long-run evolution of cross-country relative per capita carbon emissions (REPC) and intensity (RCI) vis-à-vis countries' two factors: industrial and services sectors' output. Unlike other researchers, we employed two visual tools of the distribution dynamics approach and used a panel of 217 countries. We ranked the countries based on the two factors and grouped them into four quartiles (Q1 to Q4) for each factor, resulting in eight subsamples. The results suggested long-run absolute convergence in REPC (RCI) only among highly industrialized (Q3 and Q4) countries. However, two to four convergence clubs emerged within the remaining subsamples. Besides a few (many) of the least (the most) industrialized countries converging towards the global average RCI, clubs occur at levels significantly below or above the worldwide average. The convergence was more (less) significant and towards higher (lower) REPC and RCI values for economies with low (high) industrialization. We constructed a policy priority list consisting of the least services-oriented (Q1) countries with REPC (RCI) values of 3 (7.4) and 20 (30) percent probability of further divergence from the global average in the coming years. From the perspective of climate policies aiming at reducing and converging carbon emissions, these countries require the urgent development and implementation of coordinated, bespoke policies and ongoing monitoring.